Study of reliability indicators of electromagnetic starters ПMЛ-2100 - Korobskyi, V.; Vasiuk, V.; Kostenko, A. (Energy and Automation, 2025)
The replacement of standard silver-based contact components with experimental copper-based contact assemblies has been proposed. To assess the functionality and operational feasibility of the experimental contacts, climatic testing of the contact materials was conducted. Through the evaluation of changes in contact resistance and the mass of copper-based contact material samples with thermodynamically stable additives, along with petrographic analysis of their interaction products, the transition resistance and corrosion resistance of electrical contact materials in chemically active environments were assessed. The study demonstrated stable transition resistance and high corrosion resistance of the investigated copper materials in environments containing NH3 and CO2+H2O. To determine the performance of the starters, tests on switching wear resistance were conducted. These studies were performed for standard contact components of electromagnetic starters ПМЛ-2100O4 and metal-ceramic contact components based on copper with metallic additives and defined thermodynamically stable compounds. To enhance the reliability of the contact system of electromagnetic starters and relays as a whole, it is proposed to replace standard contact components with copper-based contact components. Key words: reliability of electromagnetic starters, copper-based contact materials, transition resistance, corrosion resistance, switching wear resistance, climatic testing.